Agelotoxin: a phospholipase A(2) from the venom of the neotropical social wasp cassununga (Agelaia pallipes pallipes) (Hymenoptera-Vespidae) - Costa, Helena [UNESP]; Palma, Mario Sergio [UNESP] (Elsevier, 2000)
The neotropical wasp Agelaia pallipes pallipes is aggressive and endemic in southeast of Brazil, where very often it causes stinging accidents in rural areas. By using gel filtration on Sephadex G-100, followed by high performance reversed phase chromatography in a C-18 column under acetonitrile/water gradient, the agelotoxin was purified: a toxin presenting phospholipase A(2) (PLA(2)) activity, which occurs under equilibrium of three different aggregation states: monomer (mol. wt 14 kDa), trimer (mol. wt 42 kDa) and pentamer (mol. wt 74 kDa). The enzyme presents high sugar contents attached to the protein chain (22% [w/w]) and a transition of the values of pH optimum for the substrate hydrolysis from 7.5 to 9.0, under aggregation from monomer to pentamer. All the aggregation states present Michaelian steady-state kinetic behavior and the monomer polymerization caused a decreasing of phospholipasic activity due a non-competitive inhibition promoted by the formation of a quaternary structure. The PLA(2) catalytic activity of agelotoxin changes according to its state of aggregation (from 833 to 12533 micromol mg(-1) min(-1)) and both the monomeric and oligomeric forms present lowest activities than the PLA(2) from Apis mellifera venom and hornetin from Vespa basalis. Agelotoxin is also a very potent direct hemolysin; the monomer of agelotoxin presented hemolytic actions until 200 times higher than the PbTx from P. paulista, 740 times higher than the PLA(2) from A. mellifera, 570 times higher than that of neutral PLA(2) from N. nigricolis and about 1250 times than that of cardiotoxin from Naja naja atra venom.